Efficacy and Accuracy of ABO Blood Group Determination from Saliva - Pawan Motghare; Lata Kale; Aarti S Bedia; Sonal Charde (Journal of Indian Academy of Oral Medicine and Radiology, 2011)
Objectives: The saliva was first analyzed for the presence of anti-A and anti-B hemagglutinins in 1928. However, it was not been utilized as evidence in criminal investigations because of insufficient techniques available at that time. Hence, the present study was designed to evaluate feasibility of ABO group in medicolegal cases by determining the efficacy and accuracy of ABO blood group determination from saliva and to determine the pattern of antigen secretion in saliva in family members. Methods: A total of 200 subjects (101 males and 99 females) studied. Out of these. 100 subjects were taken at random (sample I) and 100 subjects were taken from 25 families (sample I0. The blood group of each subject was determined from saliva by absorption-inhibition method. Results: The present study showed that 83% subjects are secretors of antigen in saliva. If the subject was secretor, one of his/her parents was essentially a secretor. If both parents were secretor both the children in the family were secretors. Conclusion Results can be utilized for identification of subjects, ruling out identification, determination of inheritance in medicolegal cases.